Peran Sistem Informasi dalam Transformasi Bisnis Digital - Nugroho, Mahendra Adhi; Mirani, Erna; Arianisari, Septiningdyah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Digital transformation is a must for companies in facing the competitive business era. Information Systems has a role in Digital Business Transformation by emphasizing the importance of efficient information system integration. This study uses a qualitative method with an analytical approach and literature study. Data is taken from various source searches such as books, scientific journal articles, and research reports The appropriate sources will be analyzed against discussions related to the role of information systems in the digital transformation of businesses in companies. Data analysis was carried out qualitatively consisting of data reduction, data presentation, and conclusion drawn. The results of the analysis show that information systems play a key role in managing operations, improving individual performance, and supporting the company's strategic decisions. In the context of digital transformation, the integration of people/employees, business, and technology components is an important factor in optimizing the benefits of digitalization. Strong leadership is needed to change the company's culture to be customer-oriented and able to adapt to changing market needs. By understanding the role of information systems and the integration of digital transformation components, companies can improve operational efficiency, respond to market changes more dynamically, and create added value for customers